1996
DOI: 10.1007/bf02784175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manganese supply on thyroid hormone metabolism in the offspring of manganese-depleted dams

Abstract: The present study was performed to investigate the effect of manganese (Mn) supply on metabolism of thyroid hormones in the rat. A study with rats was carried out over two generations. Female rats were raised with a Mn-deficient diet (0.1 mg Mn/kg), and mated to produce a second generation. The male rats of the second generation were used as subjects for the investigation. They were divided into five groups and fed diets with Mn concentrations of 0.1, 0.5, 2.2, 10, and 46 mg/kg for 40 d. For assessment of thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
4
9
2
Order By: Relevance
“…Obviously, the correlations between dietary Mn and the activities of tissue TSOD, MnSOD, and copper-zinc superox ide dismutase in broiler breeders need to be further investigated. In addition, dietary Mn induced a signifi cant decrease in plasma T 3 level in the current study, which further confirmed the previous results in rats (Buthieau and Autissier, 1983;Eder et al, 1996). Fur thermore, the results from both Eder et al (1996) and Van der Geyten et al (1999) implied that the decreased plasma T 3 level due to Mn supplementation might be related to the decreased hepatic 5′-deiodinase enzyme activity, which is a key enzyme of thyroid hormone metabolism in converting T 4 into the biological active T 3 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Obviously, the correlations between dietary Mn and the activities of tissue TSOD, MnSOD, and copper-zinc superox ide dismutase in broiler breeders need to be further investigated. In addition, dietary Mn induced a signifi cant decrease in plasma T 3 level in the current study, which further confirmed the previous results in rats (Buthieau and Autissier, 1983;Eder et al, 1996). Fur thermore, the results from both Eder et al (1996) and Van der Geyten et al (1999) implied that the decreased plasma T 3 level due to Mn supplementation might be related to the decreased hepatic 5′-deiodinase enzyme activity, which is a key enzyme of thyroid hormone metabolism in converting T 4 into the biological active T 3 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, dietary Mn induced a signifi cant decrease in plasma T 3 level in the current study, which further confirmed the previous results in rats (Buthieau and Autissier, 1983;Eder et al, 1996). Fur thermore, the results from both Eder et al (1996) and Van der Geyten et al (1999) implied that the decreased plasma T 3 level due to Mn supplementation might be related to the decreased hepatic 5′-deiodinase enzyme activity, which is a key enzyme of thyroid hormone metabolism in converting T 4 into the biological active T 3 . The decreased plasma T 3 level might be involved in the improvement of thermotolerance, because hy perthyroidism accelerated the basal metabolic rate and oxidative metabolism and then resulted in oxidative damage (Asayama et al, 1987;Pereira et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…We also observed Mn 2+ accumulation in other organs of the head and neck region, which are not shielded by the bloodbrain barrier, such as the pituitary, thyroid and other endocrine glands. Although the specific function of Mn 2+ in these glands is not fully elucidated, it seems to be involved in important processes such as protection against oxidative injury (26,27) and post-translational modifications of components in the secretory pathway, such as those involved in thyroid hormone production (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…In theileriosis, schizontinfected cells may disseminate through the lymphoid tissues into thyroid glands and cause damage [9]. On the other hand, there are reports that changes in some of the micronutrients (selenium, copper, cobalt, zinc, manganese, and iodine) affect thyroid function [10][11][12]. In addition, recent studies evidenced that the decrease in the serum trace elements during ovine theileriosis, could interfere with the protective antioxidant mechanisms of RBCs [13], resulting in the anaemia.…”
Section: Introductionmentioning
confidence: 99%